Statistical Analysis of the Reliability of a Decision Obtained by the TOPSIS Method - Simanavičienė, Rūta; Cibulskaitė, Jovita (Lithuanian Journal of Statistics, 2019)
The tasks of making the most appropriate decisions taking into account a number of criteria are dealt with in variousfields such as engineering, industry, finance, economics and others. If the aim is to arrange the alternatives in a priority lineaccording to quantitative attributes, then multiattribute decision-making methods are suitable. Analysts using these methods usuallydo not take into account initial data errors – deviations in attribute values, in which case the decision may be unreliable. In thisarticle, several statistical analysis methods are proposed for the multicriteria decision to measure reliability: formulation of statisticalhypotheses and calculation of confidence intervals for parameters. Based on statistical analysis results, conclusions about thereliability of a multicriteria decision obtained using the TOPSIS method are formulated.
Keywords: multicriteria problem; reliability of decision; TOPSIS method; statistical hypothesis; confidence interval